1978
DOI: 10.1021/ac50030a014
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of a Kel-F-graphite composition electrode for general voltammetric applications

Abstract: different ion-pair association constants. The data for KBr are given in Table I.Once a value of E°is well established for a particular metal/metal-ion electrode, it is possible to determine potentiometrically the ion-pair formation constants of all the soluble 1:1 salts of that metal by application of the equation:where (M+) = antilog (E -E°MiM+)/0.05916 and the experimental values of E are corrected for liquid junction potentials. ACKNOWLEDGMENT I am grateful to Ward B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 20 publications
1
42
0
Order By: Relevance
“…The above XPS data indicated that housing carry-over occurred during polishing. Previous workers have indicated that housing carry-over significantly decreased the reversibility of electrochemical reactions at glassy carbon electrodes and indicated that glass housing material was preferable over Kel-F in that regard (29). An experiment was performed to investigate the influence of housing carry-over on electrode performance.…”
Section: Resultsmentioning
confidence: 99%
“…The above XPS data indicated that housing carry-over occurred during polishing. Previous workers have indicated that housing carry-over significantly decreased the reversibility of electrochemical reactions at glassy carbon electrodes and indicated that glass housing material was preferable over Kel-F in that regard (29). An experiment was performed to investigate the influence of housing carry-over on electrode performance.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting need for direct trace-level carbohydrate sensing has been partially solved by the development of electrochemical detection systems which try to make use of the electrooxidation of these compounds in highly basic solution (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The principal difficulty encountered in this approach is that the carbohydrates exhibit a large overpotential for oxidation at the carbon electrodes commonly used in conventional liquid chromatography/ electrochemical detection (LC/EC).…”
Section: Introductionmentioning
confidence: 99%
“…Examples are polyvinyl chloride (PVC) [195], epoxy resin [196], Kel-F [197], wax [198], ceramics [199], silicone rubber [200], amongst others.…”
Section: Carbon Composite Electrodesmentioning
confidence: 99%